Mothers' and daughters' beliefs about factors affecting preadolescent girls' body satisfaction. (March 2015) - McLaughlin, Elizabeth A.; Belon, Katherine E.; Smith, Jane Ellen; Erickson, Sarah J.
Highlights: A qualitative study explored preadolescent girls' body image. Preadolescent girls described factors affecting how they felt about their bodies. Their mothers also identified factors affecting their daughters' feelings about their bodies. Mothers as a group named similar themes to daughters as a group. Specific mother–daughter dyads did not tend to agree on the themes they named. Abstract: Body dissatisfaction is common in preadolescent girls. In this qualitative study, preadolescent girls ( N = 145) wrote descriptions of factors that made them feel good and bad about their bodies. Their mothers ( N = 145) also wrote about factors they believed made their daughters feel good and bad about their bodies. Statements were coded using thematic analysis. Chi-square analyses examined mother–daughter dyad agreement, and differences in influential factors based on ethnic identity. Despite general agreement in overall themes, results indicated limited agreement within mother–daughter dyads. Specifically, one significant result was detected: mothers and their daughters agreed on the importance of teasing as a negative influence on body satisfaction. There was one significant difference based on ethnic identity, with Hispanic girls mentioning more frequently than White girls that physical activity/exercise helped them feel good about their bodies. Recommendations are made for family-based interventions to support the body image of preadolescent girls.